2011
DOI: 10.5586/asbp.2011.003
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of aba in flower induction of Pharbitis nil

Abstract: Flowering of plants is controlled by hormones among which both stimulators and inhibitors are present. The role of abscisic acid (ABA) in flower induction of the short day plant Pharbitis nil was shown in our experiments through exogenous applications and endogenous level determination of the hormone in cotyledons of seedlings grown under special light conditions.The application of ABA to cotyledons or shoot apices during the first half of a 24-h long inductive night inhibits flowering. The same compound appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, a number of hormones can inhibit photoperiodic flower induction, e.g., auxins, ethylene, abscisic acid, and methyl jasmonate [20][21][22]24,[40][41][42][43]. It was proposed that the exogenous JAMe applied just before the inductive night inhibited the flowering in Pharbitis nil probably by stimulating ethylene production [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of hormones can inhibit photoperiodic flower induction, e.g., auxins, ethylene, abscisic acid, and methyl jasmonate [20][21][22]24,[40][41][42][43]. It was proposed that the exogenous JAMe applied just before the inductive night inhibited the flowering in Pharbitis nil probably by stimulating ethylene production [22].…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that these two members of the ARFs, which mediate auxin-induced gene expression responses, may regulate late stamen development [45]. The arf6-2 arf8-3 double mutant, as well as male-sterile JA-mutants (coi1-1, opr3), are defective in anther dehiscence, exhibit shorter filaments and produce unviable pollen grains [13,42,46]. It was revealed that auxin acts through JAs to control proper flower development, because ARF6 and ARF8 are required for the expression of JA biosynthetic pathway genes (DAD1, LOX2, AOS, and OPR3) in flower buds and consequently regulate JAs biosynthesis, which in turn activate MYB21 and MYB24.…”
Section: Discussionmentioning
confidence: 99%
“…Gibberellin can not only terminate vegetative growth to induce flowering transition, but also hinder flower formation [ 22 ], thus playing a dual role in the process of flower formation. In Arabidopsis , abscisic acid inhibits floral transformation by promoting the expression of FLC or interacting with the DELLA protein [ 23 ]; however, it can also promote the formation of flower buds, thereby also having a dual purpose [ 24 ]. The flowering transition of plants is not regulated by a single phytohormone, but by a variety of phytohormones [ 25 ].…”
Section: Introductionmentioning
confidence: 99%